Menstrual and reproductive factors and risk of breast cancer: A case-control study in the Fez region, Morocco. - Mohamed Khalis; Barbara Charbotel; Véronique Chajès; Sabina Rinaldi; Aurélie Moskal; Carine Biessy; Laure Dossus; Inge Huybrechts; Emmanuel Fort; Nawfel Mellas; Samira Elfakir; Hafida Charaka; et al. (PLoS ONE, 2018)
Breast cancer is the most common cancer in women worldwide. In the Moroccan context, the role of well-known reproductive factors in breast cancer remains poorly documented. The aim of this study was to explore the relationship between menstrual and reproductive factors and breast cancer risk in Moroccan women in the Fez region.A case-control study was conducted at the Hassan II University Hospital of Fez between January 2014 and April 2015. A total of 237 cases of breast cancer and 237 age-matched controls were included. Information on sociodemographic characteristics, menstrual and reproductive history, family history of breast cancer, and lifestyle factors was obtained through a structured questionnaire. Conditional logistic regression models were used to estimate odds ratios and 95% confidence intervals for breast cancer by menstrual and reproductive factors adjusted for potential confounders.Early menarche (OR = 1.60, 95% CI: 1.08-2.38) and nulliparity (OR = 3.77, 95% CI: 1.98-7.30) were significantly related to an increased risk of breast cancer, whereas an early age at first full-term pregnancy was associated with a decreased risk of breast cancer (OR = 0.41, 95% CI: 0.25-0.65).The results of this study confirm the role of established reproductive factors for breast cancer in Moroccan women. It identified some susceptible groups at high risk of breast cancer. Preventive interventions and screening should focus on these groups as a priority. These results should be confirmed in a larger, multicenter study.